PENGARUH METODE MODELNG THE WAY TERHADAP HASIL BELAJAR PELAJARAN BAHASA INDONESIA SISWA KELSA IV MI NW BUNGTIANG - Bisyrulhafy; Wawan Mulyadi Purnama; Kalsum (Al-mujahidah, 2022)
This research was conducted with the aim of finding out the effect of the way modeling method on the learning outcomes of class IV students at MI Hidayatul Ikhwan NW Bungtiang. This type of research uses a quantitative approach with a pre-experimental type of research and the research design used is posttest-only control group desigen, that is, this research consists of an experimental group and a control group and the two groups were not given a pre-test because the two groups were selected. randomly so that they are considered the same before treatment is given. By using the modeling the way learning method, the sample for this research was 27 class IV students. This research was carried out for 2 weeks. The data collection technique used in this research is a test of student learning outcomes which are analyzed using descriptive and inferential statistics. The data obtained is also analyzed and processed using the SPSS v 24 program. The results of the research show that there is an influence of the modeling the way learning method on lesson learning outcomes Indonesian language for class IV students at MI NW Bungtiang, which means that the influence of the modeling the way learning method is very effective in improving the learning outcomes of Indonesian language lessons for class IV students at MI NW Bungtiang.